Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering